PREVALENSI KEJADIAN BURNOUT SYNDROME DAN HUBUNGAN DENGAN FAKTOR – FAKTOR YANG MEMPENGARUHI PADA DOSEN PRIA FAKULTAS KEDOKTERAN UNIVERSITAS UDAYANA - Prasetya Sudarsana Mahaputra, Dewa Made; Purnawati, Susy; Indah Sri Handari Adiputra, Luh Made; Tirtayasa, Ketut (E-Jurnal Medika Udayana, 2022)
Workers who cannot handle the stress at work will result in burnout syndrome, especially men who work as lecturers. This study aims to determine the prevalence of burnout syndrome in male lecturers and the relationship with the factors that influence it. The analytical cross-sectional research design in this study involved 91 male lecturer respondents who worked at the Faculty of Medicine, Udayana University in 2021. The data were analyzed using Chi-Square and Spearman Rank. The frequency of occurrence of burnout syndrome were 62 (68.1%) respondents with no sign, 25 (27.5%) respondents with little sign, 3 (3.3%) respondents with severe risk and 1 (1.1%) respondent with very severe sign. The study also showed that there was no significant correlation between age and burnout syndrome (p=0.238); there was a significant correlation between marital status and burnout syndrome (p=0.004); there was no significant correlation between years of service and burnout syndrome (p=0.428); there is a significant correlation of individual factors on burnout syndrome (p=0.000); there was no significant correlation of organizational factors on burnout syndrome (p=0.099); there was no significant correlation between work environment and burnout syndrome (p=0.301).